Plasticity and phase transition in ramp-compressed single-crystal zirconium - I Adamou; N Amadou; M A Nassirou Hassan; A Moussa Hassane; A Batouré (Journal of Physics Communications)
Non-Equilibrium Molecular Dynamics Simulations have been used to investigate plasticity and phase transition in single-crystal zirconium under ramp compression, with piston maximum velocities ranging from 600 to 1400m. s ^−1 . The zirconium is found to yield via twinning deformation. Then, a direct transition from the α -phase to the high-pressure β -phase is observed, in agreement with recent experimental observations, under picosecond laser compression using ultrafast x-ray diffraction diagnostics. As the maximum ramp velocity is increased from 600 to 1400m. s ^−1 , the onset pressure of the phase transition is found to evolve from 22.6 ± 0.15 to 24.1 ± 0.4 GPa while the increase in the temperature behind the phase transition front varies from 179 ± 6 to 784 ± 48 K. The mechanism of this transition at the atomic level is consistent with the Burgers mechanism. Since the transition occurs after twinning plastic deformation, a sizeable fraction of fcc atoms is observed, which increases as the ramp evolves into a shock wave. These observations are consistent with previous theoretical simulations and experiments and contribute to understanding the response of single-crystal zirconium under dynamic compression.